Positioned To Kill: A New Approach to the Question of Military Violence - Korber, Ilana (PINS-Psychology in Society, 2026)
South Africa is a highly militarised society in which all white men, if not all citizens are positioned within a military discourse. This positioning has serious effects on the practices and options available to the subjects. While numerous studies emanating from a host of disciplines have been conducted on the experiences of conscripts and on the SADF in general, little, if any, research has focused on killing itself. As this is so critical an aspect of war and simultaneously one of the greatest taboos of our culture, it seems an important area of investigation particularly in South Africa where young men arc conscripted and often forced to participate under threat of harsh consequences. This research was motivated by the desire to understand how ordinary people become participants in legalised killing. These young men are positioned within a military discourse within which killing and atrocities take place. For those who are concerned about the psychological sequelae of participation in these activities, it is crucial to understand how it is that these men are able to carry them out. This paper attempts such an explanation.